Vascular aging phenotypes in Russian population — biological, social, and behavioral determinants - O. P. Rotar; M. A. Boiarinova; K. M. Tolkunova; E. V. Moguchaia; A. S. Alievа; A. V. Orlov; E. P. Kolesova; A. M. Erina; D. A. Usoltsev; V. N. Solntsev; E. I. Baranova; A. O. Konradi; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To assess the association of cardiovascular risk factors with various vascular aging phenotypes using the St. Petersburg population sample as part of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study.Material and methods. The current analysis, performed within the ESSE-RF multicenter observational study, included 1600 St. Petersburg residents. The participants filled out a questionnaire to assess risk factors. In addition, blood biochemical parameters, anthropometric characteristics, and blood pressure were evaluated. Pulse wave velocity (PWV) was assessed by applanation tonometry using the SphygmoCor device (AtCor, Australia) in 524 people. For analysis, 485 participants without prior cardiovascular events were selected. PWV ≤10 percentile of PWV for healthy individuals in each age group was considered as the criterion for supernormal vascular aging (SUPERNOVA) phenotype, the PWV ≥90 percentile — early vascular aging (EVA), the PWV of 10-90 percentile — normal vascular aging (NVA).Results. The prevalence of SUPERNOVA phenotype was 9,7%, EVA — 18,8%, NVA — 71,5%. Patients with EVA phenotype were more likely to have HTN (60,4%) in comparison with those with SUPERNOVA phenotype (17%) and, less likely — high physical activity (39,6 vs 53,2%). Obesity, hyperglycemia, insulin resistance, hypercholesterolemia, dyslipoproteinemia, and excessive alcohol consumption were significantly less common in participants with SUPERNOVA phenotype compared with those with EVA phenotype.Conclusion. In addition to HTN and dyslipoproteinemia, a significant predictor of premature aging was the cumulative effect of obesity, insulin resistance and hypertriglyceridemia. Among behavioral risk factors, higher physical activity and adequate alcohol consumption were factors associated with supernormal aging.